Fertilizer Subsidy Policy and its Economic Implications in Nepal - Upadhyay, Namdev; Bhandari, N.; Gairhe, S.; Kafle, N.; Sapkota, M. (Journal of Agriculture and Environment, 2019)
Available with full text.